Costs, resource utilization, and treatment patterns for patients with metastatic melanoma in a commercially insured setting - Toy, Edmond L.; Vekeman, Francis; Lewis, Michael C.; Oglesby, Alan K.; Duh, Mei Sheng (Current medical research and opinion, 2015)
To estimate real-world healthcare costs, resource utilization, and treatment patterns among metastatic melanoma (MM) patients who received a therapy recommended in current treatment guidelines during 2011 and 2012, following approval in the US of novel therapies (ipilimumab and vemurafenib). Administrative claims data were used in a retrospective, longitudinal, open cohort study. Adult MM patients were identified using ICD-9 codes. Therapy-based patient cohorts and index dates were defined by the first receipt of a therapy of interest: ipilimumab, vemurafenib, paclitaxel (alone and in combination), interleukin-2, dacarbazine (alone and in combination), or temozolomide. The follow-up period extended until the end of eligibility or data availability. A multivariate regression model was used to compare outcomes of the ipilimumab and vemurafenib cohorts, controlling for baseline and demographic characteristics. Direct healthcare costs (2013 US dollars) and utilization (incidence rates) were measured on a per-patient-per-month (PPPM) basis for each treatment cohort. Treatment patterns were assessed, including the frequency of patients receiving a second therapy of interest. The study population included 834 patients (265 ipilimumab, 234 vemurafenib, 174 paclitaxel, 104 interleukin-2, 46 dacarbazine, and 11 temozolomide). Costs ranged from $10,879 PPPM (temozolomide) to $35,472 PPPM (ipilimumab). Adjusted total costs were $18,337 PPPM higher for the ipilimumab vs. the vemurafenib cohort (p < 0.001), primarily due to higher outpatient costs. Multivariate analysis did not find significant differences in resource utilization between ipilimumab and vemurafenib, except that ipilimumab patients had fewer outpatient visits (excluding treatment visits). Ipilimumab and vemurafenib patients received a second therapy of interest (12% and 11%, respectively) less frequently than interleukin-2 and dacarbazine patients. The cost and resource utilization burden of MM is high and varies substantially across treatment cohorts. The two novel therapies, ipilimumab and vemurafenib, have quickly been adopted and are the most frequently used therapies. The results observed during the approximately 6 month follow-up period may not be representative of the full clinical experience of patients with MM.